Engineering a ceramic piston pump to minimize particle formation for a therapeutic immunoglobulin: A combined factorial and modeling approach. Issue 1 (15th August 2022) - Roffi, Kirk; Sebastião, Israel B.; Morel, Alexandre
Abstract: During fill‐finish manufacturing, protein‐pump surface interactions can induce subvisible particle (SVP) formation which poses a risk to drug product quality and patient safety. Despite this risk, there have been no concerted efforts to understand the effects of piston pump design on SVP formation. We've systematically varied the design of the piston‐cylinder interface to minimize SVP formation for a therapeutic immunoglobulin. The clearance factor, surface roughness factor, and their combined interaction significantly affected particle concentrations, quantitated by light obscuration and microflow imaging. Optimized pump designs reduced particle levels by 1–2 orders of magnitude compared to the off‐the‐shelf equipment. At the piston surface, scanning electron microscopy revealed evidence of protein film abrasion, a process which ejects SVPs from the piston‐cylinder interface as wear debris. Computational fluid dynamics and quartz crystal microbalance were applied to simulate fluid flow and protein adsorption phenomena in the pump respectively. The risk of protein film abrasion was modeled along a hypothetical Stribeck curve, thereby interconnecting design parameters, lubrication conditions, and SVP formation. Our findings support implementation of a modular pump platform with interchangeable pistons; this approach would enable the pump design to be customized based on each protein's propensity to form SVPs. This flexible approach can benefit pharmaceutical manufacturers and patients alike by accelerating tech transfer and improving process control. Abstract : In this collaborative research, we have optimized the design of a ceramic filling pump by combining factorial experiments, modeling, and simulation. Optimized pump designs reduced subvisible particle levels by 1–2 orders of magnitude compared to the off‐the‐shelf equipment. This approach offers a unique engineering perspective by connecting design parameters, lubrication conditions, and subvisible particles levels.